A síndrome da morte da Braquiaria sp - Moreira Gomes, Giovana (Universidade Federal do Tocantins, 2022)
Pastures are the basis of livestock, as they are part of the diet of production animals. Brachiaria is one of the most important pastures, with several of its cultivars used in cattle feeding, it is resistant to pests and brings benefits such as providing excellent vegetation cover, presenting a high response to fertilization and having good seed production. However, there are also the damages that affect this pasture, such as the brachiaria death syndrome, in addition to being a demanding grass from the nutritional aspect, it needs fertile soils and is susceptible to water stress. The brachiaria death syndrome consists of degradation and death due to the sum of three factors: plant malnutrition, water stress and disease attack. Therefore, the study of this syndrome is extremely important, as it brings many losses to the producer, such as the loss of pasture and consequently financial.